Audio Sensing Aid based Wireless Microphone Emulation Attacks Detection - Wang Shan-shan; Luo Xing-guo; Li Bai-nan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The wireless microphone network is an important PU network for CRN, but there is no effective technology to solve the problem of microphone evaluation attacks. Therefore, this paper propose ASA algorithm, which utilizes three devices to detect MUs, and they are loudspeaker audio sensor (LAS), environment audio sensor (EAS), and radio frequency fingerprint detector (RFFD). LASs are installed near loudspeakers, which have two main effects: One is to sense loudspeakers’ output, and the other is to broadcast warning information to all SUs through the common control channel when detecting valid output. EASs are pocket voice captures provided to SU, and utilized to sense loudspeaker sound at SU’s location. Utilizing EASs and energy detections in SU can detect primary user emulation attack (PUEA) fast. But to acquire the information of attacked channels, we need explore RFFDs to analyze the features of PU transmitters. The results show that the proposed algorithm can detect PUEA well. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3424